An environmental friendly plasma oxynitrocarburising technology with excellent performances. (September 2022) - Lu, Yangyang; Wu, Jiqiang; Wang, Dandan; Hu, Jing
Abstract: In this study, an environmental friendly plasma oxynitrocarburising technology (PNCO) was developed. The results indicated that a multi-layer microstructure consisted of a thin oxide layer, thicker compound layer and diffusion layer was obtained by PNCO. And the performances of the samples by PNCO were even a little better than those by QPQ, with the wear rate of 1.39 × 10 −3 g (N m) −1 and 1.42 × 10 −3 g (N m) −1, corrosion weight loss rate of 0.39% and 0.40% by PNCO and QPQ, respectively. Highlights: Novel environmental friendly Plasma Oxynitrocarburising (PNCO) technology was primarily developed. A multi-layer microstructure was formed by PNCO. Nanostructured oxide film was dynamically formed and reduced in the utmost surface layer during PNCO.